The Changing of the Social Stratification Pattern in Contemporary China - Tan, Bee Piang (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2013)
Communist societies and capitalist societies present two distinct social stratification patterns. The nature of stratification pattern has changed radically since China shifted from a socialist society to a market economy. The factor that determines people's social status has become different. This paper is proposed to discuss how the social stratification pattern has changed over the last three decades in China. While the social stratification in many other countries remains relatively consistent over time, China appeared to be an exception in the twentieth century. Since 1980, the inconsistency of people in China’s upward and downward social mobility has characterized China's economic reform experience for more than 30 years.